Testing industrial laboratory dispersion method of Multi-Walled Carbon Nanotubes (MWCNTs) in aqueous medium (2019)
The carbon nanotubes (CNTs) dispersion has gained interest in recent years due to its multiple applications in fields such as electronics, concrete, optics, environmental, automotive, marine and aeronautics coatings. In this sense it is necessary to develop stable dispersions of CNTs. On a laboratory scale the method of preparation of the CNTs is usually done using sonication, but this method is not appropriate to obtain CNTs dispersions on a larger scale. This work studies Multiwalled Carbon Nanotubes (MWCNTs) in aqueous medium comparing an industrial laboratory dispersion method vs traditional sonication. A factorial experimental design was performed, considering as variables: dispersion method, type of surfactant and use of a rheological modifier. The samples were prepared according to the full factorial DoE and properties such as electrical conductivity and pH were studied. Stability measurements were carried out over time and charge stability studies were performed using zeta potential measurements. The results shown the best combination of variables for the electrical conductivity was: dispersion method, sonication; dispersant, TX-100; rheological modifier, present. Although the results show that an improvement in CNTs dispersion is not achieved with the grinding and the use of industrial additives, the additive Disperbyk 2012 presented the highest value of electrical conductivity as a lonely compound, but the final electrical conductivity obtained when using it was not so high, it indicates that this additive must have specific conditions of activation, which implies that a further experimental work is required in order to get a suitable working window that allows a combination of variables with greater industrial application. © Published under licence by IOP Publishing Ltd.